Morphological and developmental plasticity in larvae of physalaemus santafecinus (anura: leiuperidae) in response to chemical cues of different predators - Gómez, Valeria Isabel (2011)
Many antipredator responses are mediated or induced by the ability of the prey to identify chemical cues of predators. The presence of chemicals produced by predators may alert tadpoles to the presence of the predators, and a heightened response to alarm cues or predator presence may increase the possibility of prey survival. We examined changes in morphology, and growth and development rates of Physalaemus santafecinus tadpoles reared in the presence of chemical cues of water beetles (Hydrophillidae) and a fish (Characidae). We recorded the time to metamorphosis, as well as weights of metamorphic individuals to determine if the larval stage is accelerated. The experiments were performed under microcosm conditions, with three treatments—chemical cues from fish, water beetles,and a control group. Each treatment was replicated 30 times. To obtain independent data from different variables, treatments were conducted on individual larvae in separate containers. The principal results were, as follow. (1) Larval morphology was significantly affected by the presence of a predator. (2) Control tadpoles were significantly larger than those subjected to the other two treatments (cues of water beetles and fish). (3) Growth and development rates did not differ significantly among any treatments. (4) Neither time to metamorphosis nor weights of metamorphs varied significantly among treatment. Our results suggest that tadpoles are able to perceive predators by chemical cues released in the water, and P. santafecinus tadpoles alter their morphology to chemical cues that indicate predation. However, chemical cues of predators had no detectable effect on growth rate and developmental rates of these tadpoles.